DEVELOPING POP-UP BOOK OF CHEMICAL HOUSEHOLD TOPIC FOR JUNIOR HIGH SCHOOL LEVEL - Priscylio, Ghery; Marsya, Rini Fath; Latisma, Latisma; Andromeda, Andromeda (JTK (Jurnal Tadris Kimiya), 2020)
This study aimed to develop pop up book on Chemical in Household topic. Â Method of the study used Research and Development by 4-D stages model; define,design,develop and disseminate. Validation sheet and practically questionnaire were the instrument to collect the data. The pop up book was validated by four experts, 2 lecturers from the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 1 lecturer of FBS Fine Arts, Universitas Negeri Padang and 1 junior high school science teacher. The practicality of the instructional materials was carried out on 1 science teacher and 27 eighth grade students at SMP Negeri 21 Padang. The data obtained were analyzed by using Cohen Kappa Formula. The validity test of the Â Pop Up bookÂ obtained an average value of kappa 0.87 moment with a very high category and a practicality test for the book based on the results of data analysis from teachersâ€™ and student questionnaires. The response of teachersâ€™ questionnaires obtained a 0.89 kappa moment value with a very high practicality category. Â The response of studentsâ€™ questionaires got an average moment value of kappa 0.83 with a very high practicality category. The result also showed that the Pop Up book can increase students' interest to learn and understand science lessons in junior high school level.